1990
DOI: 10.1148/radiology.174.2.2153310
|View full text |Cite
|
Sign up to set email alerts
|

Gliomas: classification with MR imaging.

Abstract: The findings at magnetic resonance (MR) imaging in a group of 36 pathologically verified supratentorial gliomas were analyzed and compared with the biopsy diagnoses (a) to determine whether MR imaging could be used to classify astrocytic-series tumors into a three-tiered system of low-grade astrocytoma, anaplastic astrocytoma, and glioblastoma multiforme; and (b) to evaluate MR imaging features that may aid in this classification. The MR characteristics evaluated were crossing of the midline, edema, tumor sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
104
1
4

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(115 citation statements)
references
References 0 publications
5
104
1
4
Order By: Relevance
“…In a study by Dean et al (6), only approximately 82% of the tumor grades estimated by MR were correct and the main two parameters suggestive of high-grade lesions were mass effect and intra-tumoral necrosis or cyst formation. Although enhancement was more often characteristic of high-grade lesions, 10 to 38% of the high-grade gliomas did not enhance (7) and 15 to 20% of low-grade gliomas did enhance.…”
Section: Introductionmentioning
confidence: 96%
“…In a study by Dean et al (6), only approximately 82% of the tumor grades estimated by MR were correct and the main two parameters suggestive of high-grade lesions were mass effect and intra-tumoral necrosis or cyst formation. Although enhancement was more often characteristic of high-grade lesions, 10 to 38% of the high-grade gliomas did not enhance (7) and 15 to 20% of low-grade gliomas did enhance.…”
Section: Introductionmentioning
confidence: 96%
“…Glioblastoma is an aggressive World Health Organization Grade IV malignancy with a survival rate of less than 1 year [47]. Patients are typically older than 40 years and present with symptoms of headache, memory loss, motor or language deficits, personality change or seizure [47].…”
Section: Neoplastic Malignant Glioblastomamentioning
confidence: 99%
“…Patients are typically older than 40 years and present with symptoms of headache, memory loss, motor or language deficits, personality change or seizure [47]. Imaging of glioblastoma typically demonstrates an infiltrating, heterogeneously enhancing lesion with mass effect within the supratentorial white matter that may cross the midline [47].…”
Section: Neoplastic Malignant Glioblastomamentioning
confidence: 99%
“…Edema may be present with meningiomas (DEAN et al, 1990), whereas minimal peritumoral edema was observed in choroid plexus tumors (TURREL et al, 1986). T2-weighted images were used to reconstruct edema volume because edema is better seen in T2-weighted sequence (DEAN et al, 1990).…”
mentioning
confidence: 99%
“…T2-weighted images were used to reconstruct edema volume because edema is better seen in T2-weighted sequence (DEAN et al, 1990). On the other hand, the software used offers various methods that facilitate the evaluation of the difference between two volumes by combining of the volumes into a single view.…”
mentioning
confidence: 99%